"Ducking, diving and playing along": Negotiating everyday heteroerotic subjectivity in the field. (30th August 2019) - Mphaphuli, Memory; Griffin, Gabriele
Abstract : Purpose: The purpose of this paper is to explore the fieldwork dilemmas a young, female, heterosexual, indigenous South African researching everyday negotiations around heterosexuality within township families encountered in negotiating her own heteroerotic subjectivity within the field. Design/methodology/approach: A heterosexuality studies approach is here combined with a critical feminist research methodological perspective. Findings: The paper argues that researchers are often unprepared for having to negotiate their erotic subjectivity within the field and that such negotiations can be compromising to the researcher in a variety of ways. Practical implications: The paper suggests that more might be done to prepare researchers for negotiating identity aspects such as sexuality in the field since that negotiation impacts on one's research and the researcher's sense of self in the field. Social implications: The paper critically interrogates what negotiating one's erotic subjectivity in the field might mean. Originality/value: Little is published on female researchers negotiating their heteroerotic subjectivity in the field. The paper contributes original insights on this from fieldwork carried out by an indigenous heterosexual female researcher in South African townships. It raises important issues about the conduct of fieldwork in (non-)compromising and agentic ways.